Avaliação do perfil de miRNA alterados no plasma de pacientes infectados com o vírus ZIKA - ANA CAROLINA CARVALHO SILVA (2022)
The Zika virus (ZIKV) is an arbovirus member of the family Flaviviridae and genus Flavivirus generally transmitted by mosquitoes of the genus Aedes. The clinical presentation of ZIKV is not specific (fever, skin rash, arthralgia, myalgia, anorexia and asthenia) and can be confused with other diseases, especially dengue and Chikungunya. In 2015, the first cases of ZIKV infection in Brazil were reported, as well as the association of the infection with the development of microcephaly and Guillain-Barré syndrome. The immunological and molecular mechanisms related to the response to infection with ZIKV have yet to be elucidated. The identification of molecular mechanisms responsible for the modulation, in the host, of several pathways in response to ZIKV is the first step towards finding potential therapeutic targets for the control of infection and treatment of symptoms. In the last decade it has been demonstrated that microRNAs (miRNAs), small RNA molecules of 22 nucleotides, are involved in the regulation of gene expression in virtually all cellular processes. miRNAs have also been identified as important plasma biomarkers, as they are secreted by cells or released during tissue damage and infections. It is known that different viral infections induce a change in the expression profile, as well as in the content of miRNAs circulating in the plasma of infected patients. However, there are still no studies that have studied the importance and alteration of circulating miRNAs during infection with ZIKV. In this work, we evaluated the circulating miRNAs profiles of plasma samples that were collected from patients in the acute and convalescent phases of ZIKV infection and from healthy individuals in the same endemic region. The miRNA profile of the groups was obtained and analyzed. We observed that infection with ZIKV caused changes in the profile of circulating miRNAs, as expected. This profile was different from convalescent patients and healthy patients. Using bioinformatics and systems biology tools, we predict potential targets of altered miRNAs as well as the signaling pathways they potentially control. Among the twenty-four differentially expressed miRNAs (DEMs), we highlight miR-146, miR-125a-5p, miR-30-5p and miR-142-3p identified and related to signaling pathways modulated during infection. The results presented here are an effort to open new avenues for the key roles of miRNAs during ZIKV infection.